Assessing institutional and environmental parameters of agricultural water use in South Asia: evidences from the Indo-Gangetic Basin - Xenarios, Stefanos; Sharma, Bharat R. (2011)
The Indo-Gangetic Basin encompasses most of the fertile landholdings in South Asia. However, low agricultural productivity is observed in the four riparian countries - India, Pakistan, Nepal and Bangladesh - by nailing down rural welfare. Accusations are directed at the inability of water supply sector to ensure high productivity rates and security of subsistence farmers. However, little is known about the demand side and farmers? perceptions towards the effects of water use on agricultural productivity. To this aim, we conduct an economic assessment through a stated preference approach on crucial institutional and environmental related parameters of agricultural water that could enhance productivity potential. Also, vital socio-demographic elements are examined as influential factors. The analysis is based on an extensive research survey accomplished in selected clusters along the Indo-Gangetic Basin.